A novel missense mutation in ISCA2 causes aberrant splicing and leads to multiple mitochondrial dysfunctions syndrome 4 - Al-Hassnan, Zuhair; AlDosary, Mazhor; AlHargan, Aljouhra; AlQudairy, Hanan; Almass, Rawan; Alahmadi, Khaled Omar; AlShahrani, Saif; AlBakheet, Albandary; Almuhaizea, Mohammad A.; Taylor, Robert W.; Colak, Dilek; Kaya, Namik (Frontiers in Psychiatry, 2024)
Background: ISCA2 deficiency has been linked to an autosomal recessive disorder known as multiple mitochondrial dysfunctions syndrome 4 (MMDS4). The disorder is characterized by leukodystrophy and neuroregression. Currently, most of the reported patients who carry a homozygous founder (NM_194279.2:c.229G>A:p.Gly77Ser) variant are from Saudi Arabia.We described a patient who was subjected to a full clinical evaluation, including metabolic, neurological, and radiological examination. Standard genetic testing including whole exome sequencing coupled with autozygome analysis was undertaken, as were assessments of mitochondrial DNA (mtDNA) copy number and mtDNA sequencing on DNA extracted from blood and cultured fibroblasts. Functional workup consisted of splicing assessment of ISCA2 using RT-PCR, a biochemical assessment of complex I status using dipstick assays, and mitochondrial respiration measurements using a Seahorse XFp analyzer.We present the clinical and functional characterization of a novel and homozygous ISCA2 missense variant (NM_194279.3:c.70A>G:p.Arg24Gly), a change leading to aberrant splicing in a patient presenting with neuroregression, generalized spasticity with exaggerated deep tendon reflexes and head lag, and progressive loss of acquired milestones. The novel variant was fully segregated in the wider family and was absent in a large control cohort, ethnically matching in-house exomes, local databases such as CGMdb and Saudi Human Genome Program, and in ClinVar.Our analyses reveal that the variant is pathogenic disrupting normal ISCA2 splicing and presumably leading to a truncated protein that result in disturbance of metabolic pathways in patient-derived cells.